Metal-free multicomponent cascade reactions of homopropargylic amines and acyl chlorides as well as potassium thiocyanate and diiodine: an access to thiazine imides. Issue 33 (8th August 2018) - Wu, Jing; Kong, Yuanfang; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract : A novel metal-free multicomponent cascade reaction was developed for the construction of thiazine imides. Abstract : A novel metal-free multicomponent cascade reaction was developed for the construction of thiazine imides. This four-component cascade reaction had advantages of mild reaction conditions, wide substrate scope and good atom economy. Four new bonds were formed in one pot via a 6- exo-dig iodothiolation cyclization of homopropargylic amines. The corresponding E -configurational thiazine imide products possess an exocyclic vinyliodide functional group.